Bird Composition Changes in Different Vegetation Physiognomies of a Dry Enclave in Colombia - Zuluaga-Carrero, Juliana (2021)
[Introduction]: Distinct seasonality of the dry enclave benefits endemisms and species with restricted distribution; although, during the rainy season, this distribution may vary, being broader to take advantage of resources from other ecosystems. [Objective]: Our study aims to study variations occurring in birds in different physiognomies existing in an elevational gradient in a tropical dry forest during the rain period. [Methodology]: We used 72 simultaneous sampling units for birds and plants in nine sites belonging to three vegetation physiognomies (riparian, hillsides, and scrub forests) in three altitude bands. We established two response variables, bird abundance and richness, and four independent variables: tree richness, basal area, altitude band, and site. [Results]: We found that the upper band corresponds to the azonal orobiome of the humid tropical zonobiome and has a greater richness of avifauna and less floristic richness, while the lower zone represents a tropical alternohydric zonobiome, with less diversity of birds and high floristic diversity. The least richness of birds was found in riparian forests and the greatest in hillside forests, with a low turnover. [Conclusions]: During the rainy season, there is a low altitudinal turnover of species in the hillside forests and may be explained by floristic heterogeneity. Likewise, riparian forests deserve attention due to their low bird richness and plants, aspects that could be considered in the establishment of protected areas in dry ecosystems.